Financial incentives to work in the context of a complex reform package and growing wages: the Polish experience 2005-2011 - Michal Myck; Adrian Domitrz; Leszek Morawski; Aneta Semeniuk (Baltic Journal of Economics, 2015)
We examine the consequences of changes in work incentives in Poland between 2005 and 2011 resulting from a complex tax and benefit reform package and substantial real wage growth. While marginal and participation tax rates (PTRs) in the majority of analysed cases fall as a result of the introduced reforms, the conclusions from looking at replacement rates (RRs) for the population eligible for means tested benefits are generally different. These suggest that despite significant tax giveaways incentives on the labour market weakened for families with children and for those eligible to safety net benefits. Yet despite these negative policy implications, we show that work incentives improved substantially over the period due to significant real wage growth. When analysing the effect of the reforms on financial incentives to work, we often find conflicting conclusions when using the PTRs and RRs to reflect financial attractiveness of employment. This is not necessarily surprising, but serves as a note of caution on the use of each of them independently.
Keywords: J21; J38; 330; work incentives; tax and benefit reforms; microsimulation